Vein mechanism simulation study for deep vein thrombosis early diagnosis using CFD - Ibrahim, Nabilah; Abd Aziz, Nur Shazilah; Abd Manap, Abreeza Noorlina (IOP Science, 2017)
Using a Computational Fluid Dynamics (CFD) technique, this work focus on the analysis of pressure, velocity, and vorticity of blood flow along the popliteal vein. Since the study of early stage of Deep Vein Thrombosis (DVT) becomes essential to prevent the pulmonary embolism (PE), those three parameters are analysed to assess the effect of different opening between two valves of a normal popliteal vein. When only one valve is simulated, the result of pressure shows that the highest and lowest velocities are 15.45 cm/s and 0.73 cm/s, respectively. From the visualization of observed data, however, the different size of orifice between the first and second valves influencing the velocity and vorticity of the blood flow. The rotational motion of blood particle at the same region increases the probability of blood accumulating which is associated with the development of thrombus. Thus, a series of experiment has been conducted by changing the size of valve orifice for the first and second valves along the vein distribution. The result of the CFD simulation shows a significant variation in blood flow in terms of velocity and vorticity.